Plasmon-enhanced fluorescence of PbS quantum dots for remote near-infrared imaging. Issue 1 (11th November 2014) - Wu, Ke; Zhang, Junpei; Fan, Shanshan; Li, Juan; Zhang, Chao; Qiao, Keke; Qian, Lihua; Han, Junbo; Tang, Jiang; Wang, Shuai
Abstract : Gold nanoparticles enhance the fluorescence of PbS quantum dots upon excitation with near infrared laser to implement remote imaging. Abstract : Gold nanoparticles with nanoscale protrusions can be synthesized by seed-mediated growth in favor of tuning the surface plasmon band towards the near-infrared regime. Electromagnetic field enhancement makes significant contribution to improve fluorescence emission of PbS quantum dots in the near-infrared window, identifying their application in remote imaging by collecting the scattered fluorescence of their hybrids.